PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR IPS KELAS V SEKOLAH DASAR - Intan, Muh Nur (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2022)
The goal of this study was to see how the cooperative fun make a match technique may be utilized to teach Social Sciences. This research takes a quantitative approach to learning and employs a real experimental learning strategy. This experiment involved a total of 34 pupils. In testing and tests, the Taro Yamane formula is utilized. Multiple choice quizzes based on events surrounding the announcement were used to gather data. A biserial relationship, the quality of the K-R 21 equation, discriminatory power, and difficulty index were used to determine the validity and reliability of this research instrument. The lesson test had a post-test score of 74.56, while the control group had a score of 67.65.According to findings from SD Negeri 1 Topa's investigation. The test results show the t arithmetic value of 2.690 > t table and sig value of 0.011 < 0.05. That is, there is a significant difference between the post-test results of the experimental group and the control group. Based on the post-test differences that emerged, it can be concluded that the make a match learning model is more feasible and includes a positive impact than other learning models on social studies subjects for fifth grade elementary school students land 1 Topa.